ESG performance and corporate value: Analysis from the stakeholders’ perspective - Zheng, Yuhua; Wang, Baosheng; Sun, Xiaoyang; Li, Xuelian (Frontiers in Environmental Science, 2022)
Based on the panel data of China’s A-share non-financial listed enterprises from 2011 to 2020, we empirically explore whether EGS performance can significantly promote corporate value and how to promote it, from the stakeholders’ perspective. We find that: 1) ESG performance significantly improves corporate value. 2) Both media attention and analyst coverage play an intermediary role in the impact of ESG performance on corporate value. 3) Further analysis of the single dimension of ESG illustrates that environment (E) and social responsibility (S) have a positive impact on corporate value, but the effect size of social responsibility (S) is smaller, and there is no evidence for a significant relationship between governance responsibility (G) and corporate value. 4) The heterogeneity analysis shows that ESG performance of non-heavily polluting enterprises has a significant positive effect on corporate value, but not on heavily polluting enterprises. Meanwhile, ESG performance of enterprises with a low percentage of institutional investor ownership has a significant positive effect on corporate value, but not with a high percentage. Overall, our study shows that high-quality ESG performance triggers the attention of media and analysts, which in turn promotes corporate value by raising stakeholder pressure. We also analyze the possible causes of heterogeneous results from the perspective of stakeholders, and put forward reasonable suggestions to promote ESG performance and corporate value, as well as protect the interests of stakeholders.